Kantianism for Animals A Radical Kantian Animal Ethic - Müller, Nico Dario (The Palgrave Macmillan Animal Ethics Series, 2022)
This open access book revises Kant's ethical thought in one of its most notorious respects: its exclusion of animals from moral consideration. The book gives readers in animal ethics an accessible introduction to Kant's views on our duties to others, and his view that we have only 'indirect' duties regarding animals. It then investigates how one would have to depart from Kant in order to recognise that animals matter morally for their own sake. Particular attention is paid to Kant's 'Formula of Humanity,' the role of autonomy and the moral law, as well as Kant's notions of practical reason and animal instinct. The result is a deliberately amended version of Kantianism which nevertheless remains faithful to central aspects of Kant's thought. The book's final part illustrates the framework's use in applied contexts, addressing the issues of using animals as mere means, the ethics of veganism and vegetarianism, and environmental protection. Nico Dario Müller shows how, when furnished with duties to animals, Kant's moral philosophy can be a powerful resource for animal ethicists.